ANALISIS PREFERENSI MINAT BACA MAHASISWA TERHADAP BACAAN FIKSI DAN NONFIKSI DI UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Parulian Sibuea; Berkat Sakti Perangin Angin; Shafira Oktarin Ramadani; Zaskia Azra Dumila; Muhammad Farel (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study was conducted to examine more deeply the reading interest tendencies of university students toward two main types of reading materials, namely fiction and non-fiction, within the context of higher education. Using a quantitative approach with a descriptive research design, the study involved 39 students who were selected as research participants through a simple random sampling technique to ensure that each student had an equal opportunity to be included. The survey instrument employed in this study underwent validity and reliability testing to ensure that the measurement tool was accurate and consistent in collecting data.The results indicate that students’ interest in reading fiction is higher than their interest in non-fiction materials. This tendency suggests a stronger preference for fiction reading. The difference in interest between the two categories is influenced by several factors, including stronger emotional engagement with fictional works, more varied and appealing language styles, and the presence of narrative elements that stimulate imagination and foster emotional connection with readers. Based on these findings, this study recommends strengthening literacy programs in higher education institutions. Such efforts are essential to encourage greater interest in non-fiction reading materials, which play a strategic role in expanding scientific knowledge and supporting students’ academic needs in a more comprehensive manner.